Prevalence of iron deficiency anemia in the indigenous population in regions of Brazil: an integrative review (Research, Society and Development, 2021)
Iron deficiency anemia is a global health problem caused by a long period of deficit between the amount of biologically available iron in the body and its organic need, reducing the number of hemoglobin and the oxygen transport capacity made by this protein. In this context, the general objective of this project is to observe the epidemiological aspects of iron deficiency anemia in rural and urban indigenous populations in Brazil. Having as specific objectives: To describe the prevalence of iron deficiency anemia in this population; assess the incidence of anemia in the indigenous population; compare epidemiological data in different regions and ethnic groups in Brazil. Therefore, an integrative literature review study will be developed, with a descriptive and comparative procedure, using the bibliography of iron deficiency anemia in indigenous populations in Brazil as a data source. The study will be conducted through the selection of studies in the databases: Academic Google, Scielo – Scientific Electronic Library Online, Lilacs – Latin American and Caribbean Center for Health Sciences Information and Pubmed – US National Library of Medicine following a search strategy according to the descriptors: "Iron deficiency anemia", "Epidemiology", "Indigenous", "Brazil", "Indigenous population" and "Iron deficiency anemia", with a time universe of 10 years (2011-2021).